Codesharing and airline partnerships within, between and outside global alliances - Tobias Grosche; Richard Klophaus (Journal of Air Transport Management, 2024)

Airline Market Concentration in Europe - Tobias Grosche (Digitalization Across Organizational Levels, 2022)

Consumer surplus analysis of selected long-haul air transport routes connecting Germany with California and China - Richard Klophaus; Tobias Grosche (Research in Transportation Economics, 2020)

Market concentration in German air transport before and after the Air Berlin bankruptcy - Tobias Grosche; Richard Klophaus; Adam Seredyński (Transport Policy, 2020)

Competition for long-haul connecting traffic among airports in Europe and the Middle East - Tobias Grosche; Richard Klophaus; Adam Seredyński (Journal of Air Transport Management, 2017)

Impact of timetable synchronization on hub connectivity of European carriers - Adam Seredyński; Tobias Grosche; Franz Rothlauf (Journal of air transport studies, 2016)
This paper evaluates the net impact of timetable synchronization on the connectivity of the key European carriers at their main hubs. We measure hub connectivity using a weighted connectivity score (WCS) that takes into account the number and the trip time related quality of flight connections. Based on WCS, we compare hub performance resulting from the existing schedule against a random expectation calculated from multiple randomized schedule simulations. In each simulated schedule scenario we randomly vary the flight departure and arrival times within the operation hours at a hub and at outbound stations keeping all other flight parameters from the real schedule unchanged. We observe that the timetable synchronization leverages hub connectivity of most analyzed airlines by 40% to 60%. The highest increase of connectivity is achieved by medium-sized carriers that operate peaky wave systems with flights concentrated in many short and non-overlapping banks, as well as by carriers that organize their flights in directional waves. The lowest increase isachieved by airlines that operate at highly congested airports. At most hubs, connections to long-haul flights operated with wide-body aircraft are better synchronized than connections between short-haul flights.

Hubs at risk: Exposure of Europe's largest hubs to competition on transfer city Pairs - Tobias Grosche; Richard Klophaus (Transport Policy, 2015)

An airline connection builder using maximum connection lag with greedy parameter selection - Adam Seredyński; Franz Rothlauf; Tobias Grosche (Journal of air transport management, 2014)

Computational intelligence in integrated airline scheduling - Tobias Grosche (Springer, 2009)
An airline schedule represents the central planning element of each airline. In general, the objective of airline schedule optimization is to find the airline schedule that maximizes operating profit. This planning task is not only the most important but also the most complex task an airline is confronted with. Until now, this task is performed by dividing the overall planning problem into smaller and less complex subproblems that are solved separately in a sequence. However, this procedure is only of minor capability to deal with interdependencies between the subproblems, resulting in less profitable schedules than those being possible with an approach solving the airline schedule optimization problem in one step. In this work, two planning approaches for integrated airline scheduling are presented. One approach follows the traditional sequential approach: existing models from literature for individual subproblems are implemented and enhanced in an overall iterative routine allowing to construct airline schedules from scratch. The other planning appraoch represents a truly simultaneous airline scheduling: using metaheuristics, airline schedules are processed and optimized at once without a separation into different optimization steps for its subproblems

Simultaneous airline scheduling - Tobias Grosche; Franz Rothlauf (Advances in computational intelligence in transport, logistics, and supply chain management, 2008)
Currently, there are no solution approaches available to construct and optimize airline schedules within a single model. All existing approaches decompose the problem into smaller and less complex subproblems and solve those subproblems separately. This chapter presents a metaheuristic for simultaneous airline scheduling where several different subproblems are integrated into one single optimization model, except for crew scheduling. The problem-specific metaheuristic uses an adaptive procedure for operator selection to allow an efficient choice between a variety of different operators. Experiments are conducted as proof-of-concept and to calibrate free parameters. Comparing different search strategies and studying operator probabilities show that efficiently solving the airline scheduling problem requires the application of both, local and recombination-based search operators.

Air Travel Itinerary Market Share Estimation - Tobias Grosche; Franz Rothlauf (2007)

Gravity models for airline passenger volume estimation - Tobias Grosche; Franz Rothlauf; Armin Heinzl (Journal of air transport management, 2007)
This paper presents two gravity models for the estimation of air passenger volume between city-pairs. The models include variables describing the general economic activity and geographical characteristics of city-pairs instead of variables describing air service characteristics. Thus, both models can be applied to city-pairs where currently no air service is established, historical data is not available, or for which factors describing the current service level of air transportation are not accessible or accurately predictable. One model is limited to city-pairs with airports not subject to competition front airports in the vicinity, while the other model includes all city-pairs. Booking data of flights between Germany and 28 European countries is used for calibration. Both models show a good fit to the observed data and are statistically tested and validated. (C) 2007 Elsevier Ltd. All rights reserved.

Automated Concept Evolution - Tobias Grosche; Anne Defaweux; Maria Karapatsiou; Alberto Moraglio; Alex Shenfield (2003)

A Conceptual Approach for Simultaneous Flight Schedule Construction with Genetic Algorithms - Tobias Grosche; Armin Heinzl; Franz Rothlauf (Applications of evolutionary computing : proceedings / EvoWorkshops 2001: EvoCOP ... Como, Italy, April 18 - 20, 200, 2001)